Modelling the release of nitrogen from controlled release fertiliser: Constant and decay release - Trinh, T.H. (Academic Press, 2015)
Urea, when applied to crops is vulnerable to losses from volatilisation and leaching. Controlled release urea enhances nitrogen use efficiency by plants which not only increases the crop yields but also contributes towards environmental pollution control in terms of the alleviation of hazardous gaseous emissions and water eutrophication. This study proposes a multi-diffusion model that simulates nitrogen release from coated urea particles for both the constant and decay release stages of urea. It is developed for multilayer included the coating and water zone, and integrates a Finite-element method (FEM) with 2D geometry to enhance the accuracy of simulation by introducing urea diffusivity in water domain as a function of its concentration. Results from the simulations agreed with preliminary experimental data to a standard error of estimate (SEE) that ranged from 0.0159 to 0.0567 in which the model successfully simulated and predicted nitrogen release from hours to days from smaller to larger particles. A more thorough investigation was then conducted for which the model not only predicted nitrogen release from coated urea but also described the internal release mechanism of urea from the core to urea-coated interface and into aqueous environment. Â© 2014 IAgrE.